Analisis Implementasi Digitalisasi Kualitas Pelayanan Publik - Aidi, Ahmadi; Budiwaluyo, Agus; Agoestyowati, Redjeki; Ahmad Junaidi, Ahmad Junaidi; Usman, Usman (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
The topic to be analysed in this paper is the digitalisation of public service quality, which is an effort to improve public services using digital technology and data. Digitalisation of public service quality focuses on providing services that are more efficient effective and more transparent. Digitalisation of public service quality is implemented in the transformation of technology from analogue to digital processes. This topic is interesting to study because it is motivated by the results of Cordella &; Lindgren et al, 2019; Ranerup & Henriksen, 2019; Wihlborg, Wirtz et al, 2019), the conclusion of their research is "Digitalisation of public service quality changes public services by promising more efficient, more effective, and more transparent". The phenomena that occur in public services in Indonesia include service discrimination, the absence of certainty of time and cost and the low level of public satisfaction with public services, raising the question of what concrete steps the government has taken to overcome these public service problems. One of these concrete steps is the implementation of digitisation using internet-based information technology in the provision of various DKI Jakarta government services to the community. The writing of the article was carried out with a quantitative descriptive analysis method, data sources in the form of primary data and secondary data. Primary data collection by distributing questionnaires through google form. The results of primary data collection were processed and analysed using Ms Excell. The research location was conducted in the city of Jakarta as a smart city or smart city, involving 325 respondents who live in Jakarta with a minimum education requirement of high school equivalent, minimum age 21 years maximum 60 years, from various professional backgrounds including TNI / Polri, state civil apparatus, private sector, educators, journalists and entrepreneurs. The conclusion is that by implementing digitalisation of public service quality, it has succeeded in improving the quality of services provided by the Jakarta government to the community. The recommended advice related to implementing digitalisation of public service quality is to increase innovation and increase community support for digitalisation programs through socialisation and relevant, reliable and continuous training.